The Effect of Energy Minimization on The Molecular Docking of Acetone-Based Oxindole Derivatives - Arif Fadlan; Yesaya Reformyada Nusantoro (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
In silico study by molecular docking, drug discovery, and virtual screening are useful for obtaining compounds with promising biological activity. The force fields energy minimization in molecular docking is the overall process to produce better geometry estimation and ligand-receptor affinity. In this study, the divide and conquer algorithm based on the Mikowski matrix in MarvinSketch and the conjugate gradient algorithm of Open Babel were used to minimise acetone-based oxindole derivatives in indoleamine 2,3-dioxygenase 1 (IDO1). The results showed that the binding energy produced by MarvinSketch was generally better than the binding energy obtained with Open Babel. The visualization of molecular docking results indicated that the poses and hydrogen bonding, halogen bonding and π-π interactions are different between MarvinSketch, Open Babel, and no energy minimization. The results revealed that energy minimization affects the molecular docking results.